Cardiovascular genetics: technological advancements and applicability for dilated cardiomyopathy - Kummeling, G.J.M. (Neth Heart J, 2015)
Genetics plays an important role in the pathophysiology of cardiovascular diseases, and is increasingly being integrated into clinical practice. Since 2008, both capacity and cost-efficiency of mutation screening of DNA have been increased magnificently due to the technological advancement obtained by next-generation sequencing. Hence, the discovery rate of genetic defects in cardiovascular genetics has grown rapidly and the financial threshold for gene diagnostics has been lowered, making large-scale DNA sequencing broadly accessible. In this review, the genetic variants, mutations and inheritance models are briefly introduced, after which an overview is provided of current clinical and technological applications in gene diagnostics and research for cardiovascular disease and in particular, dilated cardiomyopathy. Finally, a reflection on the future perspectives in cardiogenetics is given.